Further Understanding of the International Index of Erectile Function at 15+ Years: Confirmatory Factor Analysis and Multidimensional Scaling. (March 2014) - Bushmakin, Andrew G.; Cappelleri, Joseph C.; Symonds, Tara; Stecher, Vera J.
The objective of this study was to describe confirmatory factor analysis (CFA) and multidimensional scaling (MDS) on the International Index of Erectile Function (IIEF) to confirm the structure and to enrich understanding of the IIEF, thereby heightening appreciation of the factors and responses underlying sexual functioning for men with erectile dysfunction. Baseline, end of double-blind, and end of open-label data sets were derived from all data from 2 previously published sildenafil trials. For the CFA model, an acceptable fit of the data was shown for each data set, as indicated by a Bentler comparative fit index >0.9, statistically significant path coefficients ( t values >1.96), and (except for IIEF item 6 at baseline) statistically significant standardized path coefficients ≥0.4. For MDS modeling, the distance matrix created for each data set, based on polychoric correlations, interpreted relationships between the IIEF items in 2-dimensional space across the "sexual intercourse interference" dimension (horizontal axis) and the "sexual satisfaction" dimension (vertical axis). The 5-factor structure of the IIEF was confirmed by CFA and enriched with visual interpretation by MDS.